A visit to a differentiated classroom - Kiernan, Leslie J.; Frost, Frank; Herbert, Judith E.; Association for Supervision and Curriculum Development (Alexandria, VA: ASCD, 2001)
This video program provides an opportunity to observe a teacher who effectively addresses the learning needs of her students. Experience significant segments of a day in this teacher's 3rd/4th grade multiage classroom to understand how a differentiated classroom works
Producer, Leslie, J. Kiernan ; director, Frank Frost ; Editor, Judith E. Herbert; writer, Leslie J. Kirman, Frank Frost
Keywords: Teaching; Teaching and learning; Learning; Learning, Psychology of